Thermal transport across nanometre gaps: Phonon transmission vs. air conduction. (September 2020) - Alkurdi, A.; Adessi, C.; Tabatabaei, F.; Li, S.; Termentzidis, K.; Merabia, S.
Highlights: Atomistic calculations of phonon assisted heat transfer across nanoscale gaps between metals and between apolar materials. Development of simple analytical model to predict phonon assisted heat transfer across gaps. Comparison between phonon and air thermal conduction levels across a gap filled with molecules. Estimation of the contribution of electron-phonon processes across gaps between metals. Abstract: Heat transfer between two surfaces separated by a nanometre gap is important for a number of applications ranging from spaced head disk systems, scanning thermal microscopy and thermal transport in aerogels. At these separation distances, near field radiative heat transfer competes with heat transfer mediated by phonons. Here we quantity the contribution of phonon assisted heat transfer between apolar solids using lattice dynamics combined with ab-initio calculations. We clearly demonstrate that phonons dominate heat transfer for subnanometre gaps. Strikingly, we conclude that even in the situation where the gap is filled with air molecules, phonons provide the dominant energy channel between the two solids nearly in contact. Our results predict orders of magnitude enhanced phonon heat transfer compared to previous works and bring forward a methodology to analyse phonon transmission across nanoscale vacuum gaps between apolar materials.